Effective Organizational Functioning Capacity Needs of Rural Advisory Service Networks: A Delphi Study - Kevan W. Lamm; Alexa J. Lamm; Kristen Davis; Alissa Powell; Jyothi Swaroop Bommidi (Journal of International Agricultural and Extension Education, 2021)
This study expands on previous research within an international extensioncontext with a particular focus on identifying the capacities associated witheffective organizational functioning. A panel composed of 31 experts participated in a three-round Delphi process and identified a list of 38 specific capacities associated with effective organizational functioning related to extension networks. Among the 38 specific items, five primary themes emerged: (1) an extension network should be transparent about itspolicies, procedures, and organizational intent; (2) knowledge sharing and collaboration within an extensionnetwork is critical; (3) general policies and management guidelines should be in place; (4) the development and maintenance of intentional, long-term relationships with various actors in extension, including stakeholders, policy-decision makers, and the private sectoris critical; (5) reasonable expectations and guidelines should be established for both extensionnetwork officers and network members. The study’s results provide a guide within which extension networks and organizations may evaluate current capacities from both a developmental and strengths perspective
Keywords: capacity assessment; extension networks; organizational development